How leader humor stimulates subordinate boundary-spanning behavior: A social information processing theory perspective - Wang, Xi; Liu, Songbo; Feng, Wen (Frontiers in Psychology, 2022)
Based on social information processing theory, we provide a novel theoretical account of how and when leader humor influences subordinate boundary-spanning behavior. We develop a moderated mediation model explicating the mechanism of psychological safety and the boundary condition of subordinate interpersonal influence. Using multiwave data, we tested our research hypotheses with a sample of 452 members from 140 teams in a Chinese information technology company. Results showed that leader humor positively affects subordinate boundary-spanning behavior via increased psychological safety. Moreover, this mediated effect is stronger when subordinates have high interpersonal influence. These findings offer theoretical and practical insights into boundary-spanning activities and leader humor, which we discuss.